Effect of Cell Density and Benzyl Amino Purine on the Growth of Somatic Embryo of Citrus Mandarin Batu 55 (Citrus reticulata Blanco.) in Liquid Culture - Februyani, Nawafila; Widoretno, Wahyu; Indriyani, Serafinah (The Journal of Experimental Life Science, 2016)
Citrus mandarin Batu 55 (Citrus reticulata Blanco.) is one of Indonesian fruits commodities that have high economic value and consumers demand. The propagation of citrus mandarin by plant tissue culture generally was carried out on solid medium. The liquid culture system could increase cell multiplication therefore it became alternative method of plant propagation through somatic embryogenesis. The effect of initial cell density and Benzyl Amino Purin (BAP) concentration in liquid media were investigated. The initial cells density and right concentration of BAP given in media can increase cell proliferation of somatic embryo in liquid culture. Globular somatic embryo were cultured on Murashige and Tucker media with initial cell density 4, 6, 8 and 10 mgL-1 and BAP 0, 0.25, 0.5, and 0.75 mgL-1. Growth evaluation of somatic embryo were obtained by weighing fresh and dry weight every 2 weeks for 8 weeks for initial cell density treatment and 6 weeks of BAP treatment. The result of the research showed that cell density affect the growth of somatic embryo of citrus mandarin. Somatic embryo with low cell density showed slower growth compared than high cell density. Peak growth occured in 6th cultured with cell density 10 mgL-1. In addition to cell density, the growth of somatic embryo in liquid culture was affected by BAP. The growth of somatic embryo on the media containing BAP showed better results than without BAP. The highest BAP concentration on media showed fresh and dry weight of somatic embryo increased. In this research, growth of somatic embryo is not optimal yet because fresh and dry weights of somatic embryo still increase with high concentration 0.75 mgL-1 of BAP.Keywords: Benzyl Amino Purine, cell density, citrus mandarin, liquid medium, somatic embryo.